(untitled) (Biological Sciences - PJSIR, 2022)
Agafonova and Ryuzanov f 1,21 curried out the prccipitation and separation studies of Fe+2, Mn+2, Co+2, Ni+2 and Zn+2. Diphcnic acid has also been used [31 us u selective reagent for thcumpcromctric dctcrmlnution of thorium (IV).